IMPLEMENTATION OF THE ZACHMAN FRAMEWORK IN THEDEVELOPMENT OF THE SMART VILLAGE IT BLUEPRINT IN AFISHING VILLAGE - Nurfitria Ningsi; Noorhasanah Zainuddin; Sarimuddin Sarimuddin; Rina Sardiana Sari (PT. GWEX NET PUBLISHER, 2026)
Digital transformation in rural coastal areas is frequently impeded by fragmented data management andunstructured IT governance. This study applies the Zachman Framework to design a comprehensive SmartVillage IT Blueprint for Kangkunawe, a coastal fishing village in West Muna Regency, Indonesia. Theframework systematically maps organizational needs across six perspectives and six abstraction levels, ensuringalignment between the village's strategic vision and its technical solutions. The research proceeded throughthree phases: (1) enterprise analysis of the village's organizational structure, vision, and existing serviceprocesses; (2) Zachman matrix population across all six perspectives, yielding business, application, data,technology, and network architectures; and (3) prototype implementation of the SPEDATA module anintegrated village population data and administrative correspondence service. The resulting blueprint definesfive primary smart village service hubs: SPEDATA, e-marketplace, GIS-Health, e-tourism, and e-finance.Black-box Testing of the SPEDATA prototype confirmed 100% functional correctness across 24 test cases. TheZachman Framework is demonstrated to be effective in systematically structuring village IT governance into areproducible, scalable blueprint that directly informs prototype development.